Studio di espressione e funzione della PLCβ1 nucleare in modelli murini ed umani di cellule ematopoietiche mieloidi e linfoidi - Tagliavini, Francesca <1984> (Alma Mater Studiorum - Università di Bologna, 2012)
The aims of this work were to investigate the role of nuclear Phospholipase C beta 1 (PI-PLCβ1) in human and mouse cell lines and to identify new binding partners of nuclear PI-PLCβ1 to further understand the functional network in which the enzyme acts. The intracellular distribution of PI-PLCβ1 was further investigated in human leukaemia cell lines (NB4, HL60, THP1, CEM, Jurkat, K562). With the exception of HL60, a high endogenous level of PI-PLCβ1 was detected in purified nuclei in each of the cell lines. We found that also in Ba/F3 pro-B cells overexpressing PI-PLCβ1b the protein localize within the nucleus. Although our data demonstrated that PI-PLCβ1b was not involved in cell proliferation and IGF-1 response as shown in other cell lines (FELC and Swiss 3T3), there was an effect on apoptosis. Activation of early apoptotic markers caspase-3 and PARP was delayed in PI-PLCβ1b overexpressing Ba/F3 cells treated with 5 gr/ml mitomycin C for 24h. We performed an antibody-specific immunoprecipitation on nuclear lysates from FELC-PLCβ1b cells. Mass spectrometry analysis (nano-ESI-Q-TOF) of co-immunoprecipitated proteins allowed for identification of 92 potential nuclear PI-PLCβ1b interactors. Among these, several already documented PI-PLCβ1b interacting partners (Srp20, LaminB, EF1α2) were identified, further validating our data. All the identified proteins were nuclear, mostly localized within the nuclear speckles. This evidence is particularly relevant as PI-PLCβ1 is known to localize in the same domains. Many of the identified proteins are involved in cell cycle, proliferation and transcriptional control. In particular, many of the proteins are components of the spliceosome multi-complex, strengthening the idea that PI-PLCβ1b is involved in mRNA processing and maturation. Future work will aim to better characterize the regulatory role of PI-PLCβ1b in mRNA splicing.